Potential factors influencing the rhetorical patterns of research article discussion sections - Lulus Irawati (Universitas Syiah Kuala, 2022)
The present study reports potential factors influencing the rhetorical patterns of research articles (RA) discussion sections. The study was conducted by utilizing descriptive qualitative research. The researcher purposefully focused on investigating 10 bilingual writers who wrote both one English and one Indonesian research article. The selected writers were those who had an educational background in language and language teaching. The interviews covered the interviewees' background information, current activities, writing activities, and their rhetorical patterns of discussion sections. The interviews were conducted by utilizing the snowball technique to search for more information. The interview data were analyzed into some steps namely, transcribing the interview data, organizing data, summarizing data, and interpreting data. All data transcription was then categorized and coded. Research findings revealed that the writers' choice of move structure could be as a result of learning from other people's rhetorical patterns, believing themselves, having high self-confidence, having high writing frequency, and having high awareness in the micro and macrostructure of writing discussion sections. The Indonesian writers have opened their minds to learn and read other researchers' articles and then determine whether the patterns are suitable for them or not. The writers' starting point of experiencing to have their RA published made them believe in themselves and felt self-confident. Thus, the more they wanted to write RA, the higher they had writing frequency and awareness in the micro and macrostructure of writing discussion sections.